Growth and socio-economic status, influence on the age at menarche in school going girls. (January 2021) - Karim, Asima; Qaisar, Rizwan; Hussain, M. Azhar
Abstract: Introduction: Onset age at menarche has been considered an important indicator of reproductive maturity in females and reflects the health status of the population. The purpose of this study was to determine the mean menarcheal age and to examine whether anthropometric and socio-economic status (SES) influences age at menarche in the girls from Punjab province of Pakistan. Methods: In this population-based cross-sectional study, 10, 050 school-going girls aged 8–16 years from 35 schools across 12 districts of Punjab were recruited. Menarcheal data was obtained by using a questionnaire, while the anthropometric data were obtained by the measurements of standing height, body weight, waist, and hip circumference. The anthropometric indices of pre- and post-menarcheal girls were compared. Student's t-test, ANOVA, and post-hoc Tukey's test was applied for comparison between two and multiple groups respectively, P < 0.05 was considered statistically significant. Results: There was a normal distribution of age at menarche and mean was 12.4 years in the study population. The girls who reached menarche were found to be taller and heavier with higher BMIs, having a greater waist and hip circumference as compared to their pre-menarcheal peers. Waist-hip-ratio was less, and the waist-to-height ratio was higher in post-menarcheal as compared to pre-menarcheal girls. The girls belonging to low SES had delayed onset of menarche as compared to those belonging to middle/high SES. Conclusion: The age at menarche was associated with SES and changes in various anthropometric measurements reflecting the growth status of girls.